Developmental changes in episodic memory across early- to mid-childhood: insights from a latent longitudinal approach. Issue 3 (16th March 2022) - Canada, Kelsey L.; Hancock, Gregory R.; Riggins, Tracy
ABSTRACT: Episodic memory is a cornerstone ability that allows one to recall past events and the spatiotemporal context in which they occur. In an effort to characterise the development of this critical ability, many different tasks have been used independently to assess age-related variations in episodic memory. However, performance on memory tasks is multiply determined, and the extent to which different tasks with varying features relate to each other and represent episodic memory as a latent cognitive construct across childhood is unclear. The present study sought to address this question by exploring the feasibility of using four different laboratory-based tasks to characterise changes in episodic memory ability during early- to mid-childhood in 200 typically developing children (4–8 years). Using longitudinal data and a structural equation modeling framework, results suggest that multiple tests of episodic memory can be utilised to indicate a comparable latent construct of episodic memory ability over this period of development, and that this ability improves consistently between 4 to 8 years. Overall, results highlight that episodic memory measured as a construct increases at a similar rate over early- to mid-childhood and demonstrate the benefits of using multiple laboratory tasks to characterise developmental changes in episodic memory.